Cr-rich clinopyroxene megacrysts from the Grib kimberlite, Arkhangelsk province, Russia: relation to clinopyroxene–phlogopite xenoliths and evidence for mantle metasomatism by kimberlite melts - Kargin, AV; Sazonova, LV; Nosova, AA; Lebedeva, NM; Tretyachenko, VV; Abersteiner, A (2017)
To provide new insights into the origin of megacrysts and metasomatism of the subcontinental lithospheric mantle (SCLM), we present a detailed petrographic and geochemical investigation of clinopyroxene-phlogopite xenoliths and clinopyroxene megacrysts from the Grib kimberlite (Arkhangelsk diamond province, Russia). Clinopyroxene megacrysts and clinopyroxene from clinopyroxene-phlogopite xenoliths have similar petrography, major and trace element compositions, and are therefore classified as Cr-rich megacrysts. Geothermobarometry suggests that Cr-rich clinopyroxenes originate from within the SCLM (3.6–4.7 GPa and 764–922 °C). Phlogopite from clinopyroxene-phlogopite xenoliths have low-Ti and -Cr compositions that overlaps with phlogopite megacrysts from the Grib kimberlite. The clinopyroxene-phlogopite rocks within the SCLM are the main source for Cr-rich clinopyroxene and low-Ti phlogopite megacrysts in the Grib kimberlite matrix. Trace element compositions of studied Cr-rich clinopyroxenes have similar geochemical features to clinopyroxenes megacrysts occurrences worldwide and overlap with clinopyroxenes from phlogopite-garnet peridotite xenoliths from the Grib kimberlite. The strong depletion in Ti, Nb, Ta and to a lesser extent in Zr and Hf in clinopyroxene reflects equilibrium with Ti-oxides, such as ilmenite. The clinopyroxene-phlogopite xenoliths could be the final product of metasomatism of garnet peridotites within the SCLM beneath the Grib kimberlite. The calculated equilibrium of clinopyroxene melt compositions suggests that the metasomatic agents were derived from silicate-bearing kimberlite melts. The presence of veinlets infilled with kimberlitic mineral assemblages in clinopyroxene grains suggests that the clinopyroxene-phlogopite rocks experienced intense interactions with kimberlite melt after their formation, but before their entrainment into the host kimberlite magma. This interaction resulted in the formation of high-Ti and -Cr phlogopite and high-Ti clinopyroxene rims, zones and grains with ...